Traveling wave vibration of graphene platelet reinforced porous joined conical-cylindrical shells in a spinning motion. (1st February 2022) - Chai, Qingdong; Wang, Yan Qing
Highlights: A spinning joined conical-cylindrical porous shell reinforced with GPLs is theoretically modeled. GPL regional allocation is a key factor in tuning the vibration characteristics. Different types of porosity distributions and GPL dispersion patterns are taken into account. Traveling wave frequencies and mode shapes of the joined shell are investigated. Abstract: The present study investigates traveling wave vibration characteristics of spinning graphene platelets reinforced metal foam (GPLRMF) joined conical-cylindrical shells (JCCSs) for the first time. The Donnell's shell theory is adopted to formulate the present model, and the centrifugal force, Coriolis force as well as initial hoop tension resulting from the spin are all considered. Three types of porosity distributions and graphene platelet (GPL) dispersion patterns are taken into account. By employing the Halpin-Tsai equation and the mixture rule, the GPL reinforced material properties are determined. Governing equations are obtained by adopting Hamilton's principle, and then are solved by utilizing the power series method. After the validation with the available literature and finite element results, the effects of GPL regional allocation on vibration characteristics are particularly explored. It is found that allocating more GPLs in large-size pore regions is unbefitting for increasing traveling wave frequencies. In addition, allocating GPLs in the conical shell segment can improve traveling wave frequencies more significantly compared with that in the cylindrical shell segment or the whole JCCS.